JURIDICAL STUDY OF THE IMPLEMENTATION OF ADMINISTRATIVE MEASURES TO RESOLVE STATE ADMINISTRATIVE DISPUTES - Bambang Harianto; Abdul Rahman Maulana Siregar; Fauzan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The implementation of the Regulation of the Supreme Court of the Republic of Indonesia (PERMA) Number: 6 of 2018, dated 4 December 2018 concerning Guidelines for Settlement of Government Administrative Disputes after taking administrative measures, which is a further regulation of the provisions in Articles 75, 76 and Article 77 of Law Number 30 of the Year 2014 concerning Government Administration, bringing changes to the State Administrative Justice system in Indonesia, namely related to Administrative Efforts. This then gives rise to several problems, namely first, whether administrative measures are an obligation that must be taken first before filing a state administrative dispute lawsuit with the State Administrative Court (PTUN); secondly, what is the procedure for making objections to State Civil Service (ASN) employment disputes? The aim of this research is to analyze and describe the application of administrative efforts to state administration disputes. Normative juridical research methods are used to answer this problem. The results of the research show that administrative efforts must be carried out as legal protection for the people in State Administration disputes, and the legal procedure is to carry out objection efforts in ASN disputes as regulated in Article 129 of Law Number 5 of 2014 concerning State Civil Apparatus, and the Judge will reject the party If the plaintiff has not taken the available administrative measures.